2014
DOI: 10.4172/2161-1165.1000148
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Supplementation of Vitamin D3 on Serum Levels of Vitamin D: A Review

Abstract: and placebo (3 times daily), for 3 months. Anti-ds DNA serum levels were measured by ELISA and urine protein were measured by urine albumin creatinine ratio (UACR). Results After supplementation for 3 months, this study showed that decreased of anti-dsDNA serum levels in the supplementa-tion group was significantly greater than in the placebo group. The decreased of UACR in the supplementation group was also significantly greater than the placebo group. Conclusions Adding curcumin on vitamin D supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
(50 reference statements)
0
9
0
1
Order By: Relevance
“…A regression analysis of all reviewed studies showed a correlation of 61% which supported a consistent doseresponse relationship independent of various confounders (Jarrett et al, 2014). Additionally, the researchers found that healthy and ill individuals did not vary on response to dose, supporting a generalizable dosing schedule (Jarrett et al, 2014). In a meta-analysis of randomized controlled trials of oral vitamin D supplementation, it was found that high-dose VDS (> 800IU/day) was more beneficial in the prevention of hip fracture and any nonvertebral fracture in people 65 years and older (Bischoff-Ferrari et al, 2012).…”
Section: The Case For Vd Supplementationmentioning
confidence: 63%
See 4 more Smart Citations
“…A regression analysis of all reviewed studies showed a correlation of 61% which supported a consistent doseresponse relationship independent of various confounders (Jarrett et al, 2014). Additionally, the researchers found that healthy and ill individuals did not vary on response to dose, supporting a generalizable dosing schedule (Jarrett et al, 2014). In a meta-analysis of randomized controlled trials of oral vitamin D supplementation, it was found that high-dose VDS (> 800IU/day) was more beneficial in the prevention of hip fracture and any nonvertebral fracture in people 65 years and older (Bischoff-Ferrari et al, 2012).…”
Section: The Case For Vd Supplementationmentioning
confidence: 63%
“…A regression analysis of all reviewed studies showed a correlation of 61% which supported a consistent doseresponse relationship independent of various confounders (Jarrett et al, 2014). Additionally, the researchers found that healthy and ill individuals did not vary on response to dose, supporting a generalizable dosing schedule (Jarrett et al, 2014).…”
Section: The Case For Vd Supplementationmentioning
confidence: 88%
See 3 more Smart Citations